An examination of the importance of performances in youth and junior competition as an indicator of later success in tennis - Brouwers, J.; de Bosscher, V.; Sotiriadou, P. (Sport Management Review, 2012)
Talent identification at a young age is deemed essential for many national sporting organisations to increase the chances of success for their players on the international stage. Talent identification methods can be imprecise and national tennis associations and coaches often identify talent based on performances at youth tournaments and junior rankings. However, not much is known about the relationship between the international competition performances of young tennis players and later success. This relationship is explored in this study using comparisons based on: (a) the results of 3521 players at U14 youth tournaments; (b) the rankings of 377 junior players (U18) by the International Tennis Federation; (c) the rankings of 727 professional male players by the Association of Tennis Professionals; and (d) the rankings of 779 professional players by the Women's Tennis Association. Junior performances (U18) and performances at youth tournaments (U14) appear to have a low success rate in predicting later success. No distinct age was found at which players should start to perform in order to be successful at the professional level. It is concluded that even though good performances at young ages increase athletes` chances to become elite players, they are not a precondition for achieving later success. Therefore, this study informs talent scouts, sport development officers, coaches and high performance managers of the role that performances at international youth competitions may play in talent identification in tennis.